KAJIAN DAYA SANGGA BIOCHAR LIMBAH SAGU PADA PELINDIAN TERHADAP KETERSEDIAAN NPK DI TANAH ULTISOL - Latuponu H; Dj. Shiddieq; Abd. Syukur; E. Hanudin (Universitas Tribhuwana Tunggadewi, 2012)
This study was conducted in the greenhouse of Chemical and Soil Fertilty Lab. UGM, with the aims to find good combination of kind of biochar and NPK fertilizer and time of incubation on availability NPK in Ultisol. Randomized Complete Design was used with two factors. First factors consists of combination of biochar and NPK (control, biochar 200, 400, 600) and biochar 200+NPK, biochar 400+NPK , biochar 600+NPK.). Second factors: incubation 2 week, 4 week and 6 week. Replication was three times. The results showed that treatment of biochar 400 increased holding capasity of NPK , pH, Al-dd, CEC, Carbon, N, P and K. The best length of incubation is 4 week